LaF3 / PAN-coated Zn metal negative electrode and preparation method and application thereof
The zinc negative electrode is modified by LaF3/PAN electrospinning nanofiber membrane, which solves the problems of zinc negative electrode interface corrosion and hydrogen precipitation, achieves uniform deposition and high-temperature performance of zinc ions, and significantly improves the cycling stability of aqueous zinc ion batteries.
Patent Information
- Application Number
- CN202411309501.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-19
- Publication Date
- 2024-12-20
AI Technical Summary
The existing zinc negative electrodes have interface corrosion and hydrogen precipitation problems in aqueous zinc ion batteries, resulting in expansion and damage of the battery, and the single component protective layer cannot meet the needs of zinc ion conduction, uniform deposition environment and structural stability at the same time.
The zinc negative electrode is modified in situ by LaF3/PAN electrospinning nanofiber membrane, and the composite nanofiber membrane is constructed through electrospinning technology, combining the hydrophobicity and cyano functional groups of LaF3 and polyacrylonitrile, inhibiting the growth of zinc dendrites and improving zinc ions. conductivity.
It significantly improves the corrosion resistance and cycle stability of the zinc negative electrode, inhibits hydrogen evolution and side reactions, achieves uniform deposition and high-temperature performance of zinc ions, and extends the cycle life of the battery.
Smart Images

Figure CN119170729A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of aqueous zinc ion batteries and relates to a LaF3 / PAN@Zn metal negative electrode and a preparation method and application thereof. Background Art
[0002] High-performance energy storage technology can improve the utilization efficiency of new clean energy and is an important way to ensure a stable power supply. The most critical technical requirements for large-scale energy storage technology include good safety, low cost and environmental friendliness. Aqueous zinc-ion batteries have become one of the promising large-scale energy storage technologies due to their easy assembly and inherently safe aqueous electrolytes. The zinc metal anode has a suitable redox potential (0.76 V compared to the standard hydrogen electrode), a high theoretical specific capacity (mass specific capacity 820 mAh g −1 ; Volumetric capacity 5855 mAh cm −3 ), and is derived from abundant natural resources, it has become one of the most commercially promising anode materials for aqueous zinc-ion batteries. However, zinc metal is thermodynamically and electrochemically unstable in H2O, which inevitably leads to corrosion and hydrogen evolution at the interface. This hydrogen evolution may cause battery swelling or damage, while the accumulation of corroded zinc and its byproducts reduces the Coulombic efficiency of the zinc anode, aggravates the heterogeneity of the zinc surface, and promotes the formation of zinc dendrites. In severe cases, zinc dendrites may penetrate the separator, leading to battery failure. Therefore, improving the interfacial stability of the zinc anode and achieving uniform zinc deposition are crucial to the development of high-performance zinc anodes.
[0003] Since chemical / electrochemical reactions all occur at the zinc anode / electrolyte interface during the cycle, it is crucial to obtain a stable reaction interface. Researchers have proposed a series of strategies to construct artificial protective layers to alleviate the problems at the zinc anode interface, especially dendrites and side reactions. A variety of inorganic materials (such as TiO2, Nb2O5 and zeolites), carbon-based materials (such as graphene and carbon nanotubes) and organic polymer-based materials (such as polydopamine, polyvinylidene fluoride and poly (2-vinylpyridine)) have been explored and studied as physical protective layers to inhibit the growth of zinc dendrites and mitigate the corrosion of the zinc anode. In the prior art, organic polymers or inorganic materials are prepared into zinc negative electrode protective layers. For example, patent CN114792775A discloses a polyvinylidene fluoride (PVDF) and hexafluoropropylene (HFP) copolymer modified coating material, which reduces the electrochemical polarization behavior during zinc negative electrode electroplating / stripping. Patent CN117542947A discloses a silicon dioxide aerogel coating material coated on the surface of zinc negative electrode, which can effectively alleviate the two-dimensional growth of dendrites during the cycle of aqueous zinc ion batteries. However, most of these artificial protective layers are constructed in situ on the Zn negative electrode by scraper casting or spin coating. During the cycle, there are problems such as poor zinc ion transmission performance and easy detachment of the protective layer from the Zn surface, resulting in loss of protective effect. Additional adhesives, such as polyvinylidene fluoride (PVDF), will also hinder ion transmission and increase interface resistance, and a single organic or inorganic material cannot simultaneously meet the requirements of the ideal zinc ion interface protective layer, such as fast zinc ion conduction, uniform zinc ion concentration and zinc deposition environment, good structural stability and good volume change adaptability.
[0004] Therefore, constructing a unique interfacial protective layer with a long cycle life on the surface of the zinc negative electrode to achieve the goal of improving the corrosion resistance of the zinc negative electrode interface and inhibiting dendrites, and developing a composite multi-component interfacial protective layer with good zinc ion conductivity and good flexibility to modify zinc metal is one of the effective strategies for developing high-performance zinc negative electrodes. Summary of the invention
[0005] In view of the technical problem that a single component protective layer cannot simultaneously meet the requirements of an ideal zinc ion interface protective layer, which requires fast zinc ion conduction, uniform zinc ion concentration and zinc deposition environment, good structural stability and good volume change adaptability, the present invention proposes a LaF3 / PAN@Zn metal negative electrode and its preparation method and application. The present invention constructs a LaF3 / PAN mixed electrostatic spinning nanofiber membrane in situ on the surface of the zinc negative electrode, thereby achieving the purpose of modifying the zinc negative electrode, improving the corrosion resistance of the metal zinc negative electrode during the charge and discharge process, limiting the growth of zinc dendrites, inhibiting the occurrence of hydrogen evolution and side reactions, and thus improving the cycle stability of the aqueous zinc ion battery.
[0006] In order to achieve the above object, the technical solution of the present invention is achieved as follows: A method for preparing a LaF3 / PAN@Zn metal negative electrode, the preparation steps are as follows: (1) adding nano-LaF3 and polyacrylonitrile to an organic solvent for dispersion and dissolution to obtain a polyacrylonitrile mixed solution; (2) The zinc sheet is placed on an electrospinning receiver, and the polyacrylonitrile mixed solution is electrospinned. After drying, the LaF3 / PAN@Zn metal negative electrode is obtained.
[0007] The organic solvent in step (1) is N,N-dimethylformamide (DMF) or dimethylacetamide (DMAC).
[0008] In the polyacrylonitrile mixed solution, the molecular weight of polyacrylonitrile is 150,000, the concentration of polyacrylonitrile is 8-10wt%, and the concentration of nano-LaF3 is 1.0-1.8wt%.
[0009] In the step (2), the voltage of electrospinning is 16-18 kV, the injection speed is 0.8-1.5 mL / h, the distance from the injection head to the receiver is 10-20 cm, the receiver rotation speed is 330 r / min, and the time is 1-3 h.
[0010] The preparation method of the nano-LaF3 comprises the following steps: mixing lanthanum nitrate hexahydrate, deionized water, a surfactant and ammonium fluoride, performing a hydrothermal reaction, and then performing centrifugal washing and drying to obtain the nano-LaF3, wherein the particle size of the nano-LaF3 is 10-20 nm.
[0011] The surfactant is polyethylene glycol or hexadecyltrimethylammonium bromide.
[0012] The molar ratio of the lanthanum nitrate hexahydrate, ammonium fluoride and surfactant is 1:(3-6):0.1; the temperature of the hydrothermal reaction is 70-80°C, and the time is 12-15 hours.
[0013] The LaF3 / PAN@Zn metal negative electrode prepared by the above method is a LaF3 / PAN electrospun nanofiber membrane in situ modified on the surface of the metal zinc negative electrode.
[0014] The thickness of the LaF3 / PAN electrospun nanofiber membrane is 70-80 μm.
[0015] The drying temperature in step (2) is 60-80°C and the drying time is 9-12 hours.
[0016] The application of the LaF3 / PAN@Zn metal negative electrode in aqueous zinc ion batteries.
[0017] The specific preparation method of LaF3 / PAN@Zn metal anode is as follows: add lanthanum nitrate hexahydrate to deionized water, stir thoroughly, then add surfactant and ammonium fluoride for stirring, finally move the solution to the reactor for hydrothermal reaction, then centrifuge, wash and dry to obtain LaF3 powder, add LaF3 powder sample to organic solvent DMF or DMAC for ultrasonic dispersion to obtain LaF3 suspension (solution A). Take PAN (molecular weight: 15w) powder and add it to solution A, heat and stir at 70~80℃ until PAN is completely dissolved, and prepare a PAN solution (solution B) with a specific concentration of LaF3 uniformly dispersed. Place the zinc sheet on the electrospinning receiver, then take solution B for mixed electrospinning process, then dry at 60~80℃ for 9~12h, and finally obtain the zinc sheet modified with LaF3 / PAN composite nanofiber membrane, i.e. LaF3 / PAN@Zn metal anode.
[0018] The present invention has the following beneficial effects: 1. In the present invention, PAN provides a hydrophobic carbon skeleton and a cyano functional group that can interact with zinc ions. The fluoride ions of LaF3 inhibit the growth of zinc dendrites through coordination induction; and the high charge of lanthanum ions interacts strongly with the anions in the electrolyte, promoting the desolvation of zinc ions and accelerating their migration, thereby improving the conductivity of zinc ions. In the present invention, the LaF3 / PAN nanofiber membrane is constructed in situ on the surface of the zinc electrode by electrospinning technology in one step, and the fiber membrane and the zinc negative electrode can achieve good contact without the action of other additional binders. Therefore, the LaF3 / PAN nanofiber membrane has the inherent high porosity and flexibility of the electrospinning membrane, which can ensure the conduction of zinc ions and better adapt to the volume change of the negative electrode during the electrochemical process. LaF3 / PAN nanofiber membrane can also play a dual-component synergistic role on the basis of retaining the respective advantages of PAN and LaF3, effectively preventing the corrosion of the zinc negative electrode during the charge and discharge process, and the affinity for zinc ions helps to reduce the nucleation barrier of zinc ions and avoid uneven deposition. Therefore, electrospinning LaF3 / PAN@Zn has the advantages of inhibiting the occurrence of interfacial side reactions, accelerating the interfacial zinc ion transfer, inducing uniform and dense zinc deposition, and improving high-temperature performance, thereby realizing the development of zinc negative electrodes and zinc ion batteries with long cycle life.
[0019] 2. The present invention successfully constructs an in-situ LaF3 / PAN organic-inorganic composite electrospinning fiber membrane with "zinc-philic-hydrophobic" properties on the Zn electrode through electrospinning technology, thereby achieving the purpose of optimizing the modification of the zinc negative electrode. The membrane has good adaptability to the volume expansion during the electroplating / stripping process of the zinc negative electrode, and its "zinc-philic-hydrophobic" characteristics make the zinc negative electrode have better corrosion resistance and the effect of inhibiting the hydrogen evolution side reaction.
[0020] 3. The electrospun LaF3 / PAN@Zn metal anode prepared by the present invention was immersed in the electrolyte used in aqueous zinc ion batteries. By comparing with the control samples (blank pure zinc anode, electrospun PAN@Zn anode), it was found that the surface of the electrospun LaF3 / PAN@Zn metal anode prepared by the present invention was flat before and after the reaction, and no vertical dendrites were found ( Figure 2 (e)), while the blank pure zinc negative electrode showed more vertical dendrites after reaction ( Figure 2 In (c), the surface of the electrospun PAN@Zn negative electrode is cracked ( Figure 2 (d)), which confirms that the electrospun LaF3 / PAN@Zn anode prepared by the present invention effectively inhibits the growth of zinc dendrites (such as Figure 2 as shown).
[0021] 4. The electrospun LaF3 / PAN@Zn metal anode prepared by the present invention is applied to aqueous zinc ion batteries. According to the given data and performance diagram, it can be seen that the area capacity is 1 mAh cm -2 1 mA cm -2 At a current density of 1.547 W / m, the blank pure Zn / / Zn symmetric battery experienced a sudden drop in polarization voltage when the cycle reached 50 h, which may be caused by a short circuit in the battery. In addition, the electrospun PAN@Zn symmetric battery also experienced a short circuit in a very short time. In contrast, the electrospun LaF3 / PAN@Zn of the present invention still showed a stable polarization voltage curve after 1200 h of cycling, showing the best cycle stability. It can be seen from the given rate performance diagram that when the switching current density is from 1 to 10 mA cm -2 When the current density is increased from 1 to 20 mA cm, the pure Zn and electrospun PAN@Zn symmetric batteries show a sharp voltage short circuit phenomenon, while the electrospun LaF3 / PAN@Zn has a short circuit phenomenon when the current density is increased from 1 to 20 mA cm -2 When the current is changed from 10mA cm -2 Switch back to 1 mA cm -2 When the electrospun LaF3 / PAN@Zn symmetric battery still maintains a stable polarization voltage, it indicates that the electrospun LaF3 / PAN@Zn anode has excellent rate performance (such as Figure 3 , Figure 4 as shown).
[0022] 5. The 50°C high temperature performance of the electrospun LaF3 / PAN@Zn metal anode prepared by the present invention and the comparison samples (blank pure zinc anode, electrospun PAN@Zn anode) were tested by assembling symmetrical batteries. It can be seen that the area capacity is 1 mAh cm -2 5 mA cm -2At a current density of 1.3 2.0 ... Figure 5 as shown). BRIEF DESCRIPTION OF THE DRAWINGS
[0023] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0024] Figure 1 This is the EDS element spectrum of the electrospun LaF3 / PAN modified metal zinc negative electrode sheet prepared in Example 1 of the present invention.
[0025] Figure 2 The figures are SEM tests related to the LaF3 powder, electrospun LaF3 / PAN modified metal zinc negative electrode sheet and its comparison samples (blank pure zinc negative electrode, electrospun PAN@Zn negative electrode) prepared in Example 1 of the present invention; wherein (a) is a scanning electron microscope photo of LaF3 powder; (b) is a scanning electron microscope photo of the surface of the electrospun LaF3 / PAN@Zn negative electrode; (c) is a scanning electron microscope photo of the pure Zn negative electrode after immersion in electrolyte; (d) is a scanning electron microscope photo of the electrospun PAN@Zn negative electrode after immersion in electrolyte; (e) is a scanning electron microscope photo of the electrospun LaF3 / PAN@Zn negative electrode after immersion in electrolyte.
[0026] Figure 3 The symmetrical batteries of pure zinc (comparative application example 2), electrospun PAN@Zn (comparative application example 1) and electrospun LaF3 / PAN@Zn (application example 1) in Example 1 of the present invention have a capacity of 1 mAh cm -2 , current density is 1 mA cm -2 Long cycle performance diagram.
[0027] Figure 4 The symmetrical batteries of pure Zn (comparative application example 2), electrospun PAN@Zn (comparative application example 1) and electrospun LaF3 / PAN@Zn (application example 1) in the present invention have a capacity of 1 mAh cm -2 , rate performance diagram at different current densities.
[0028] Figure 5The battery with pure zinc (comparative application example 2), electrospun PAN@Zn (comparative application example 1) and electrospun LaF3 / PAN@Zn (application example 1) as negative electrode has a capacity of 1 mAh cm -2 , current density is 5 mA cm -2 50 ℃ high temperature long cycle performance diagram.
[0029] Figure 6 These are in-situ dendrite microscopic observation photos of zinc deposition on the pure zinc in the present invention and the electrospun LaF3 / PAN@Zn negative electrode of Example 1.
[0030] Figure 7 The impedance diagrams of capacitors assembled with the negative electrodes of pure zinc (Comparative Application Example 4), electrospun PAN@Zn (Comparative Application Example 3) and electrospun LaF3 / PAN@Zn (Application Example 2) in Example 1 of the present invention and the activated carbon AC positive electrode, respectively.
[0031] Figure 8 Different current densities (0.2A g) of the electrospun LaF3 / PAN@Zn / / AC (Application Example 2) prepared in Example 1 of the present invention, the comparative Zn / / AC (Comparative Application Example 4), and the electrospun PAN@Zn / / AC (Comparative Application Example 3) capacitors -1 ~2A g -1 )’s rate performance diagram.
[0032] Fig. 9 This is a long cycle performance diagram of the capacitors of electrospun LaF3 / PAN@Zn / / AC in Application Example 2 of the present invention, comparative application example Zn / / AC (Comparative Application Example 4), and electrospun PAN@Zn / / AC (Comparative Application Example 3). DETAILED DESCRIPTION
[0033] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0034] The raw materials used in the embodiments of the present invention are commercially available products.
[0035] Example 1 This example is the preparation of LaF3 / PAN electrospun nanofiber membrane modified zinc negative electrode (LaF3 / PAN@Zn metal negative electrode), the steps are as follows: (1) Add 30 mmol of lanthanum nitrate hexahydrate into 80 mL of deionized water, stir thoroughly, then add 3 mmol of PEG-2000 (surfactant) and 90 mmol of ammonium fluoride and stir. Finally, move the solution to a reactor for hydrothermal reaction at 70 °C for 12 h, then centrifuge, wash and dry to obtain LaF3 powder. (2) Add 0.184 g of LaF3 powder to 10 mL of DMAC and disperse by ultrasonic until the LaF3 powder is evenly dispersed in DMAC to obtain a LaF3 suspension (solution A). (3) Add 1.041 g of polyacrylonitrile (PAN) powder to solution A obtained in step (2), heat and stir at 70°C to obtain a polyacrylonitrile solution (solution B) in which LaF3 is uniformly dispersed, i.e., a 9.6 wt% PAN & 1.7 wt% LaF3 solution; (4) The zinc sheet was placed on the electrospinning receiver, and then 1 mL of solution B was taken for electrospinning; the electrospinning voltage was 18 kV, the injection speed was 1 mL / h, the distance from the injection head to the receiver was about 15 cm, the receiver speed was about 330 r / min, and the electrospinning time was about 1 h. Subsequently, it was dried at 70 °C for 12 h, and finally a zinc sheet modified with LaF3 / PAN composite nanofiber membrane with a thickness of about 70 μm was obtained, namely, LaF3 / PAN@Zn metal anode.
[0036] Comparative Example 1 This comparative example provides a method for preparing a PAN@Zn metal negative electrode, which is different from Example 1 in that lanthanum fluoride is not added for modification to prepare a PAN@Zn metal negative electrode. The specific steps are: (1) Add 1.041 g of polyacrylonitrile (PAN) powder to 10 mL of DMAC, heat and stir at 70 °C to obtain a polyacrylonitrile solution (solution A) with a PAN concentration of 9.6 wt%; (2) The zinc sheet was placed on the electrospinning receiver, and then 1 mL of solution A was taken for electrospinning; the electrospinning voltage was 18 kV, the injection speed was 1 mL / h, the distance from the injection head to the receiver was about 15 cm, the receiver speed was about 330 r / min, and the electrospinning time was about 1 h. Subsequently, it was dried at 70 °C for 12 h, and finally a zinc sheet modified with LaF3 / PAN composite nanofiber membrane with a thickness of about 70 μm was obtained, namely PAN@Zn metal anode.
[0037] Application Example 1 Application of LaF3 / PAN@Zn metal anode in aqueous zinc ion batteries: The LaF3 / PAN@Zn metal negative electrode prepared in Example 1 was punched into a disc with a diameter of 8 mm, and a glass fiber was used as a separator, a 2 M ZnSO4 solution was used as an electrolyte, and a metal gasket and a spring were used as filling materials to assemble a CR-2032 button cell and encapsulate it with an encapsulation machine, and then it was left to stand for 7 hours before the electrochemical performance test was carried out. The zinc deposition / stripping performance was tested on a blue electric charge and discharge tester using a constant current method to characterize its cycle performance and polarization potential.
[0038] Application Example 2 Application of LaF3 / PAN@Zn metal negative electrode in capacitors: The electrospun LaF3 / PAN@Zn metal anode prepared in Example 1 was punched into discs with a diameter of 8 mm. AC, acetylene black and binder (PVDF) were coated on titanium foil in a slurry with a mass ratio of 7:2:1. After vacuum drying at 80 °C, the discs were cut into electrode sheets with a diameter of 8 mm. The active loading was controlled at 1-2 mg cm -2 , used as the positive electrode. With glass fiber as the separator, 2 M ZnSO4 solution as the electrolyte, metal gaskets and springs as the filling materials, a CR-2032 button capacitor, namely the electrospun LaF3 / PAN@Zn / / AC capacitor, was assembled and packaged with a packaging machine, and then left to stand for 7 h before the electrochemical performance test.
[0039] Comparative application example 1 This comparative application example provides a zinc battery, which is different from application example 1 in that the PAN@Zn metal negative electrode obtained in comparative example 1 is used as the negative electrode of the zinc battery, and the specific steps are as follows: The PAN@Zn metal negative electrode of comparative example 1 was punched into a disc with a diameter of 8 mm, and glass fiber was used as a separator, 2M ZnSO4 solution was used as an electrolyte, and metal gaskets and springs were used as filling materials to assemble CR-2032 button cells and package them using a packaging machine, and then they were left to stand for 7 hours before the electrochemical performance test was performed. The zinc deposition / stripping performance was tested on a blue electric charge and discharge tester using a constant current method to characterize its cycling performance and polarization potential.
[0040] Comparative Application Example 2 This comparative application example provides a zinc battery. The prepared battery uses a pure Zn sheet as the negative electrode, and the remaining operations are the same as those in application example 1; the details are as follows: The Zn metal negative electrode was punched into discs with a diameter of 8 mm. Glass fiber was used as the separator, 2 M ZnSO4 solution was used as the electrolyte, and metal gaskets and springs were used as filling materials. The CR-2032 button cells were assembled and packaged using a packaging machine, and then left to stand for 7 h before the electrochemical performance test.
[0041] Comparative Application Example 3 This comparative application example provides a PAN@Zn / / activated carbon (AC) capacitor, which is different from application example 2 in that the PAN@Zn metal negative electrode obtained in comparative example 1 is used as the negative electrode of the zinc battery, and the specific steps are as follows: The electrospun PAN@Zn metal anode prepared in Comparative Example 1 was punched into discs with a diameter of 8 mm. AC, acetylene black and binder (PVDF) were coated on titanium foil in a slurry with a mass ratio of 7:2:1. After vacuum drying at 80 °C, the discs were cut into electrode sheets with a diameter of 8 mm. The active loading was controlled at 1-2 mg cm -2 , used as the positive electrode. Using glass fiber as the separator, 2 MZnSO4 solution as the electrolyte, metal gaskets and springs as the filling materials, CR-2032 button capacitors were assembled and packaged using a packaging machine, and then left to stand for 7 h before the electrochemical performance test.
[0042] Comparative Application Example 4 This comparative application example provides a zinc / / activated carbon (AC) capacitor, which is different from application example 2 in that the negative electrode is a pure zinc metal sheet, and the remaining operation steps are the same; the specific steps are: The Zn metal anode was punched into discs with a diameter of 8 mm. AC, acetylene black and binder (PVDF) were coated on titanium foil in a slurry with a mass ratio of 7:2:1. After vacuum drying at 80 °C, the discs were cut into 8 mm diameter electrode sheets with an active loading of 1-2 mg cm. -2 , used as the positive electrode. Using glass fiber as the separator, 2 M ZnSO4 solution as the electrolyte, metal gaskets and springs as the filling materials, CR-2032 button capacitors were assembled and packaged using a packaging machine, and then left to stand for 7 h before the electrochemical performance test.
[0043] Figure 1 This is the EDS elemental energy spectrum of the electrospun LaF3 / PAN modified metal zinc negative electrode sheet prepared in Example 1 of the present invention. The energy spectrum shows diffraction peaks of Zn, C, N, La and F elements, indicating that PAN and LaF3 components exist at the same time, and the LaF3 / PAN@Zn metal negative electrode is successfully prepared.
[0044] Figure 2The present invention relates to SEM tests of the LaF3 powder prepared in Example 1 of the present invention, the electrospun LaF3 / PAN modified metal zinc negative electrode and its comparative samples (blank pure zinc negative electrode, electrospun PAN@Zn negative electrode prepared in comparative example 1); wherein (a) is a scanning electron microscope photo of LaF3 powder; (b) is a scanning electron microscope photo of the surface of the electrospun PAN@Zn negative electrode; (c) is a scanning electron microscope photo of the pure Zn negative electrode after immersion in electrolyte; (d) is a scanning electron microscope photo of the electrospun PAN@Zn negative electrode after immersion in electrolyte; (e) is a scanning electron microscope photo of the electrospun LaF3 / PAN@Zn negative electrode after immersion in electrolyte. From (a), it can be seen that the prepared LaF3 powder is a nanoparticle with a size of 10-20 nm; from (b), it can be seen that the surface morphology of the electrospun LaF3 / PAN@Zn is a fiber membrane formed by the interlacing of nanowire fibers, and the surface of the fiber membrane is uniformly coated with LaF3 nanoparticles; from (c), it can be seen that the surface of the blank Zn negative electrode is uneven after being immersed in the electrolyte, and many vertical dendrite byproducts appear, which may cause the battery to short-circuit; from (d), it can be seen that there are no obvious dendrites on the surface of the electrospun PAN@Zn, but there are obvious protrusions and holes on the surface, and there are more cracks than before the reaction, but from (e), it can be seen that the surface of the electrode sheet of the electrospun LaF3 / PAN@Zn maintains a complete and uniform morphology after being immersed in the electrolyte, and there is no zinc dendrite deposition on the surface. It can be seen that the electrospun LaF3 / PAN modified Zn negative electrode can change the growth direction of the byproducts on the surface of the Zn negative electrode during the reaction, avoiding the generation of vertical dendrites.
[0045] Example 2 This example is the preparation of LaF3 / PAN electrospun nanofiber membrane modified zinc negative electrode (LaF3 / PAN@Zn metal negative electrode), the steps are as follows: (1) Add 20 mmol of lanthanum nitrate hexahydrate into 80 mL of deionized water, stir thoroughly, then add 2 mmol of PEG-2000 (surfactant) and 80 mmol of ammonium fluoride and stir. Finally, move the solution to a reactor for hydrothermal reaction at 70 °C for 12 h, then centrifuge, wash and dry to obtain LaF3 powder. (2) Add 0.116 g of LaF3 powder to 10 mL of DMAC and disperse by ultrasonic until the LaF3 powder is evenly dispersed in DMAC to obtain a LaF3 suspension (solution A). (3) Add 1.041 g of polyacrylonitrile (PAN) powder to the solution A obtained in step (1), heat and stir at 70°C to obtain a polyacrylonitrile solution (solution B) in which LaF3 is uniformly dispersed, i.e., a 9.66 wt% PAN & 1.08 wt% LaF3 solution; (4) The zinc sheet was placed on the electrospinning receiver, and then 1 mL of solution B was taken for electrospinning; the electrospinning voltage was 18 kV, the injection speed was 1 mL / h, the distance from the injection head to the receiver was about 12 cm, the receiver speed was about 330 r / min, and the electrospinning time was about 1 h. Subsequently, it was dried at 60 °C for 9 h, and finally a zinc sheet modified with LaF3 / PAN composite nanofiber membrane with a thickness of about 70 μm was obtained, namely LaF3 / PAN@Zn metal anode.
[0046] The application of LaF3 / PAN@Zn metal anode in aqueous zinc ion batteries is as follows: Aqueous zinc sulfate electrolyte was used, glass fiber was used as a separator, and the LaF3 / PAN@Zn metal negative electrode prepared in Example 2 was used as an electrode sheet to assemble a zinc / / zinc symmetric battery, and the cycle performance and polarization potential were tested.
[0047] Using aqueous zinc sulfate electrolyte and glass fiber as separator, LaF3 / PAN@Zn metal anode and activated carbon (AC) were assembled into capacitors to test capacity, rate performance and cycle stability.
[0048] Example 3 This example is the preparation of LaF3 / PAN electrospun nanofiber membrane modified zinc negative electrode (LaF3 / PAN@Zn metal negative electrode), the steps are as follows: (1) Add 10 mmol of lanthanum nitrate hexahydrate to 80 mL of deionized water, stir thoroughly, then add 1 mmol of CTAB (surfactant) and 50 mmol of ammonium fluoride and stir. Finally, move the solution to a reactor for hydrothermal reaction at 80 °C for 13 h, then centrifuge, wash and dry to obtain LaF3 powder. (2) Add 0.141 g of LaF3 powder to 10 mL of DMAC and disperse by ultrasonic until the LaF3 powder is evenly dispersed in DMAC to obtain a LaF3 suspension (solution A). (3) Add 1.041 g of polyacrylonitrile (PAN) powder to the solution A obtained in step (1), heat and stir at 70 °C to obtain a polyacrylonitrile solution (solution B) in which LaF3 is uniformly dispersed, i.e., a 9.65 wt% PAN & 1.31 wt% LaF3 solution; (4) The zinc sheet was placed on the electrospinning receiver, and then 1 mL of solution B was taken for electrospinning; the electrospinning voltage was 18 kV, the injection speed was 1 mL / h, the distance from the injection head to the receiver was about 10 cm, the receiver speed was about 330 r / min, and the electrospinning time was about 1 h. Subsequently, it was dried at 80 °C for 9 h, and finally a zinc sheet modified with LaF3 / PAN composite nanofiber membrane with a thickness of about 70 μm was obtained, namely LaF3 / PAN@Zn metal anode.
[0049] The application of LaF3 / PAN@Zn metal anode in aqueous zinc ion batteries is as follows: Aqueous zinc sulfate electrolyte was used, glass fiber was used as a separator, and the LaF3 / PAN@Zn metal negative electrode prepared in Example 3 was used as an electrode sheet to assemble a zinc / / zinc symmetric battery, and the cycle performance and polarization potential were tested.
[0050] Using aqueous zinc sulfate electrolyte and glass fiber as separator, LaF3 / PAN@Zn metal anode and activated carbon (AC) were assembled into capacitors to test capacity, rate performance and cycle stability.
[0051] Example 4 This example is the preparation of LaF3 / PAN electrospun nanofiber membrane modified zinc negative electrode (LaF3 / PAN@Zn metal negative electrode), the steps are as follows: (1) Add 20 mmol of lanthanum nitrate hexahydrate into 80 mL of deionized water, stir thoroughly, then add 2 mmol of CTAB (surfactant) and 120 mmol of ammonium fluoride and stir. Finally, move the solution to a reactor for hydrothermal reaction at 80 °C for 14 h, then centrifuge, wash and dry to obtain LaF3 powder. (2) Add 0.144 g of LaF3 powder to 10 mL of DMAC and disperse by ultrasonic until the LaF3 powder is evenly dispersed in DMAC to obtain a LaF3 suspension (solution A). (3) Add 0.815 g of polyacrylonitrile (PAN) powder to solution A obtained in step (1), heat and stir at 70°C to obtain a polyacrylonitrile solution (solution B) in which LaF3 is uniformly dispersed, i.e., 8.0 wt% PAN & 1.36 wt% LaF3 solution; (4) The zinc sheet was placed on the electrospinning receiver, and then 2 mL of solution B was taken for electrospinning; the electrospinning voltage was 18 kV, the injection speed was 0.8 mL / h, the distance from the injection head to the receiver was about 20 cm, the receiver speed was about 330 r / min, and the electrospinning time was about 2.5 h. Subsequently, it was dried at 70 °C for 11 h, and finally a zinc sheet modified with LaF3 / PAN composite nanofiber membrane with a thickness of about 75 μm was obtained, namely, LaF3 / PAN@Zn metal negative electrode.
[0052] The application of LaF3 / PAN@Zn metal anode in aqueous zinc ion batteries is as follows: Aqueous zinc sulfate electrolyte was used, glass fiber was used as a separator, and the LaF3 / PAN@Zn metal negative electrode prepared in Example 4 was used as an electrode sheet to assemble a zinc / / zinc symmetric battery, and the cycle performance and polarization potential were tested.
[0053] Using aqueous zinc sulfate electrolyte and glass fiber as separator, LaF3 / PAN@Zn metal anode and activated carbon (AC) were assembled into capacitors to test capacity, rate performance and cycle stability.
[0054] Example 5 This example is the preparation of LaF3 / PAN electrospun nanofiber membrane modified zinc negative electrode (LaF3 / PAN@Zn metal negative electrode), the steps are as follows: (1) Add 20 mmol of lanthanum nitrate hexahydrate into 80 mL of deionized water, stir thoroughly, then add 2 mmol of CTAB (surfactant) and 100 mmol of ammonium fluoride and stir. Finally, move the solution to a reactor for hydrothermal reaction at 75 °C for 12 h, then centrifuge, wash and dry to obtain LaF3 powder. (2) Add 0.133 g of LaF3 powder to 10 mL of DMF and disperse by ultrasonic until the LaF3 powder is evenly dispersed in DMF to obtain a LaF3 suspension (solution A). (3) Add 0.815 g of polyacrylonitrile (PAN) powder to solution A obtained in step (1), heat and stir at 75 °C to obtain a polyacrylonitrile solution (solution B) in which LaF3 is uniformly dispersed, i.e., a 7.72 wt% PAN & 1.26 wt% LaF3 solution; (4) The zinc sheet was placed on the electrospinning receiver, and then 3 mL of solution B was taken for electrospinning; the electrospinning voltage was 17 kV, the injection speed was 1 mL / h, the distance from the injection head to the receiver was about 15 cm, the receiver speed was about 330 r / min, and the electrospinning time was about 3 h. Subsequently, it was dried at 70 °C for 13 h, and finally a zinc sheet modified with LaF3 / PAN composite nanofiber membrane with a thickness of about 80 μm was obtained, namely LaF3 / PAN@Zn metal anode.
[0055] The application of LaF3 / PAN@Zn metal anode in aqueous zinc ion batteries is as follows: Aqueous zinc sulfate electrolyte was used, glass fiber was used as a separator, and the LaF3 / PAN@Zn metal negative electrode prepared in Example 5 was used as an electrode sheet to assemble a zinc / / zinc symmetric battery, and the cycle performance and polarization potential were tested.
[0056] Using aqueous zinc sulfate electrolyte and glass fiber as separator, LaF3 / PAN@Zn metal anode and activated carbon (AC) were assembled into capacitors to test capacity, rate performance and cycle stability.
[0057] Example 6 This example is the preparation of LaF3 / PAN electrospun nanofiber membrane modified zinc negative electrode (LaF3 / PAN@Zn metal negative electrode), the steps are as follows: (1) Add 40 mmol of lanthanum nitrate hexahydrate into 80 mL of deionized water, stir thoroughly, then add 4 mmol of PEG-2000 (surfactant) and 120 mmol of ammonium fluoride and stir. Finally, move the solution to a reactor for hydrothermal reaction at 80 °C for 15 h, then centrifuge, wash and dry to obtain LaF3 powder. (2) Add 0.139 g of LaF3 powder to 10 mL of DMF and disperse by ultrasonic until the LaF3 powder is evenly dispersed in DMF to obtain a LaF3 suspension (solution A). (3) Add 0.927 g of polyacrylonitrile (PAN) powder to solution A obtained in step (1), heat and stir at 75°C to obtain a polyacrylonitrile solution (solution B) in which LaF3 is uniformly dispersed, i.e., 8.69 wt% PAN & 1.3 wt% LaF3 solution; (4) The zinc sheet was placed on the electrospinning receiver, and then 3 mL of solution B was taken for electrospinning; the electrospinning voltage was 18 kV, the injection speed was 1.5 mL / h, the distance from the injection head to the receiver was about 16 cm, the receiver speed was about 330 r / min, and the electrospinning time was about 2 h. Subsequently, it was dried at 75 °C for 12 h, and finally a zinc sheet modified with LaF3 / PAN composite nanofiber membrane with a thickness of about 80 μm was obtained, namely LaF3 / PAN@Zn metal negative electrode.
[0058] The application of LaF3 / PAN@Zn metal anode in aqueous zinc ion batteries is as follows: Aqueous zinc sulfate electrolyte was used, glass fiber was used as a separator, and the LaF3 / PAN@Zn metal negative electrode prepared in Example 6 was used as an electrode sheet to assemble a zinc / / zinc symmetric battery, and the cycle performance and polarization potential were tested.
[0059] Using aqueous zinc sulfate electrolyte and glass fiber as separator, LaF3 / PAN@Zn metal anode and activated carbon (AC) were assembled into capacitors to test capacity, rate performance and cycle stability.
[0060] Example 7 This example is the preparation of LaF3 / PAN electrospun nanofiber membrane modified zinc negative electrode (LaF3 / PAN@Zn metal negative electrode), the steps are as follows: (1) Add 0.183 g of commercially available LaF3 powder (particle size 10-20 nm) to 10 mL of DMF and disperse by ultrasonic until the LaF3 powder is evenly dispersed in DMF to obtain a LaF3 suspension (solution A). (2) adding 0.927 g of polyacrylonitrile (PAN) powder to solution A obtained in step (1), heating and stirring at 75°C to obtain a polyacrylonitrile solution (solution B) in which LaF3 is uniformly dispersed, i.e., a 8.65 wt% PAN & 1.71 wt% LaF3 solution; (3) The zinc sheet was placed on the electrospinning receiver, and then 1 mL of solution B was taken for electrospinning; the electrospinning voltage was 18 kV, the injection speed was 1 mL / h, the distance from the injection head to the receiver was about 15 cm, the receiver speed was about 330 r / min, and the electrospinning time was about 1 h. Subsequently, it was dried at 80°C for 10 h, and finally a zinc sheet modified with LaF3 / PAN composite nanofiber membrane with a thickness of about 76 μm was obtained, namely, LaF3 / PAN@Zn metal anode.
[0061] The application of LaF3 / PAN@Zn metal anode in aqueous zinc ion batteries is as follows: Aqueous zinc sulfate electrolyte was used, glass fiber was used as a separator, and the LaF3 / PAN@Zn metal negative electrode prepared in Example 7 was used as an electrode sheet to assemble a zinc / / zinc symmetric battery, and the cycle performance and polarization potential were tested.
[0062] Using aqueous zinc sulfate electrolyte and glass fiber as separator, LaF3 / PAN@Zn metal anode and activated carbon (AC) were assembled into capacitors to test capacity, rate performance and cycle stability.
[0063] Example 8 This example is the preparation of LaF3 / PAN electrospun nanofiber membrane modified zinc negative electrode (LaF3 / PAN@Zn metal negative electrode), the steps are as follows: (1) Add 30 mmol of lanthanum nitrate hexahydrate into 80 mL of deionized water, stir thoroughly, then add 3 mmol of PEG-2000 (surfactant) and 90 mmol of ammonium fluoride and stir. Finally, move the solution to a reactor for hydrothermal reaction at 80 °C for 12 h, then centrifuge, wash and dry to obtain LaF3 powder. (2) Add 0.115 g of LaF3 powder to 10 mL of DMF and disperse by ultrasonic until the LaF3 powder is evenly dispersed in DMF to obtain a LaF3 suspension (solution A). (3) Add 0.927 g of polyacrylonitrile (PAN) powder to solution A obtained in step (1), heat and stir at 80°C to obtain a polyacrylonitrile solution (solution B) in which LaF3 is uniformly dispersed, i.e., 8.71 wt% PAN & 1.08 wt% LaF3 solution; (4) The zinc sheet was placed on the electrospinning receiver, and then 1.5 mL of solution B was taken for electrospinning; the electrospinning voltage was 16 kV, the injection speed was 1 mL / h, the distance from the injection head to the receiver was about 15 cm, the receiver speed was about 330 r / min, and the electrospinning time was about 1.5 h. Subsequently, it was dried at 65 °C for 10 h, and finally a zinc sheet modified with LaF3 / PAN composite nanofiber membrane with a thickness of about 70 μm was obtained, namely, LaF3 / PAN@Zn metal anode.
[0064] The application of LaF3 / PAN@Zn metal anode in aqueous zinc ion batteries is as follows: Aqueous zinc sulfate electrolyte was used, glass fiber was used as a separator, and the LaF3 / PAN@Zn metal negative electrode prepared in Example 8 was used as an electrode sheet to assemble a zinc / / zinc symmetric battery, and the cycle performance and polarization potential were tested.
[0065] Using aqueous zinc sulfate electrolyte and glass fiber as separator, LaF3 / PAN@Zn metal anode and activated carbon (AC) were assembled into capacitors to test capacity, rate performance and cycle stability.
[0066] Implementation effect example 1. Battery cycle performance The batteries obtained in Application Example 1, Comparative Application Example 1 and Comparative Application Example 2 were tested for zinc deposition / stripping performance on a blue electric charge and discharge tester using a constant current method to characterize their cycle performance and polarization potential; Figure 3 , Figure 4 and Figure 5 shown.
[0067] 2. In situ dendrite microscopy testing The LaF3 / PAN@Zn electrode sheet prepared in Example 1 and the pure zinc Zn electrode sheet were subjected to in-situ dendrite microscopy test to characterize their hydrogen evolution and dendrite suppression. Figure 6 shown.
[0068] 3. Zinc / / Activated Carbon (AC) Capacitor Assembly The capacitors obtained in Application Example 2, Comparative Application Example 3 and Comparative Application Example 4 were subjected to electrochemical performance tests.
[0069] Under the same assembly conditions, pure zinc (Comparative Application Example 4) and electrospun PAN@Zn negative electrode (Comparative Application Example 3) were also used with the AC positive electrode to form a capacitor, and the impedance of the battery was tested. Figure 7 The constant current method was used to test the battery at different current densities (0.2Ag -1 ~2Ag -1 )’s charge-discharge performance and cycle stability, such as Figure 8 , 9 shown.
[0070] 4. Electrochemical performance test Figure 3 and Figure 4 This is a performance comparison chart of three zinc / / zinc symmetric batteries corresponding to the electrospun LaF3 / PAN@Zn / / electrospun LaF3 / PAN@Zn negative electrode prepared in Example 1 of the present invention and the comparative example Zn / / Zn and electrospun PAN@Zn / / electrospun PAN@Zn negative electrode. Figure 2 It can be seen that at an area capacity of 1 mAh cm -2 1 mA cm -2At a current density of 1.547 W / m, the blank pure Zn / / Zn symmetric battery experienced a sudden drop in polarization voltage after 50 h of cycling, which may be caused by a short circuit in the battery. In addition, the electrospun PAN@Zn symmetric battery also experienced a short circuit in a very short time. In contrast, the electrospun LaF3 / PAN@Zn of the present invention still showed a stable polarization voltage curve after 1200 h of cycling, showing the best cycling stability. Figure 3 As can be seen from the rate performance diagram, when the switching current density increases from 1 to 10 mA cm -2 When the current density is increased from 1 to 20 mA cm, the pure Zn and electrospun PAN@Zn symmetric batteries show a sharp voltage short circuit phenomenon, while the electrospun LaF3 / PAN@Zn has a short circuit phenomenon when the current density is increased from 1 to 20 mA cm -2 When the current is changed from 10mA cm -2 Switch back to 1 mA cm -2 When , the electrospun LaF3 / PAN@Zn symmetric battery still maintains a stable polarization voltage, which indicates that the electrospun LaF3 / PAN@Zn anode has excellent rate performance.
[0071] Figure 5 The high temperature performance of three zinc / zinc symmetric batteries corresponding to the electrospun LaF3 / PAN@Zn / / electrospun LaF3 / PAN@Zn anode (i.e., application example 1) prepared in Example 1 of the present invention, the comparative example Zn / / Zn (comparative application example 2), and the electrospun PAN@Zn / / electrospun PAN@Zn anode (comparative application example 1) at 50°C. It can be seen that at an area capacity of 1 mAhcm -2 5 mA cm -2 At a current density of , the electrospun LaF3 / PAN@Zn symmetric battery operated stably for more than 500 h, while both PAN@Zn and blank pure zinc symmetric batteries suffered serious short circuits in less than 50 h, indicating that the electrospun LaF3 / PAN@Zn negative electrode has excellent high temperature resistance.
[0072] Figure 6 The in-situ dendrite microscopic observation photos of zinc deposition of pure zinc and electrospun LaF3 / PAN@Zn negative electrode in Example 1 of the present invention are shown in Figure 1. The in-situ optical microscope was used to observe the 10 mA cm −2 Zinc deposition process under current density. As the electroplating process progresses, irregular zinc protrusions appear on pure zinc, providing uneven nucleation sites for the formation of zinc dendrites, resulting in rampant growth of zinc dendrites. After 120 min of electroplating, severe hydrogen evolution and zinc dendrites occurred. However, the zinc deposition of the electrospun LaF3 / PAN@Zn negative electrode maintained a very uniform deposition throughout the electroplating process, without hydrogen evolution and zinc dendrites.
[0073] Figure 7 From the electrochemical impedance diagrams of the electrospun LaF3 / PAN@Zn / / AC capacitors prepared in Application Example 2 of the present invention and the Zn / / AC capacitors in Comparative Application Example 4 and Comparative Application Example 3, it can be seen that the electrospun LaF3 / PAN@Zn / / AC capacitor (Application Example 2) has the lowest impedance and the highest slope in the low-frequency straight line portion, indicating that it has the best zinc ion transmission capability.
[0074] Figure 8 Electrospun LaF3 / PAN@Zn / / AC prepared in Application Example 2 of the present invention and Zn / / AC in Comparative Application Example 4 and PAN@Zn@Zn / / AC in Comparative Application Example 3 at different current densities (0.2A g -1 ~2A g -1 ) of the charge and discharge rate performance diagram. Figure 7 It can be seen that although in 2A g -1 At high current density, the electrospun LaF3 / PAN@Zn / / AC capacitor has the highest initial capacity and recovers to 0.2A g -1 The highest reversible capacity can be maintained during the process, which is significantly better than the performance of pure zinc capacitors. This is due to the higher ion transport capacity of the electrospun LaF3 / PAN@Zn / / AC capacitor. This proves that the assembled electrospun LaF3 / PAN@Zn / / AC capacitor has excellent rate performance.
[0075] Fig. 9 This is a comparison chart of the long cycle performance of three types of capacitors prepared by electrospinning LaF3 / PAN@Zn / / AC prepared in Application Example 2 of the present invention, and electrospinning Zn / / AC prepared in Comparative Application Example 4 and PAN@Zn / / AC prepared in Comparative Application Example 3. Figure 8 It can be seen that after experimental verification, at a current density of 2 A / g, electrospun LaF3 / PAN@Zn / / AC has a higher initial specific capacity than pure Zn / / AC and electrospun PAN@Zn / / AC. In addition, pure Zn / / AC and electrospun PAN@Zn / / AC experienced drastic capacity decay after 2000 cycles, while electrospun LaF3 / PAN@Zn / / AC was still able to maintain a stable specific capacity after 5000 cycles, and the cycle efficiency was as high as 99.58%, showing excellent capacity retention and cycle life.
[0076] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a LaF3 / PAN@Zn metal negative electrode, characterized in that: The preparation steps are as follows: (1) adding nano-LaF3 and polyacrylonitrile to an organic solvent for dispersion and dissolution to obtain a polyacrylonitrile mixed solution; (2) Place the zinc sheet on an electrospinning receiver, take the polyacrylonitrile mixed solution for electrospinning, and obtain the LaF3 / PAN@Zn metal anode after drying.
2. The method for preparing the LaF3 / PAN@Zn metal negative electrode according to claim 1, characterized in that: The organic solvent in step (1) is N,N-dimethylformamide or dimethylacetamide.
3. The method for preparing the LaF3 / PAN@Zn metal negative electrode according to claim 2, characterized in that: The concentration of polyacrylonitrile in the polyacrylonitrile mixed solution is 8-10wt%, and the concentration of nano-LaF3 is 1.0-1.8wt%.
4. The method for preparing the LaF3 / PAN@Zn metal negative electrode according to claim 3, characterized in that: In the step (2), the voltage of electrospinning is 16-18 kV, the injection speed is 0.8-1.5 mL / h, the distance from the injection head to the receiver is 10-20 cm, and the receiver rotation speed is 330 r / min.
5. The method for preparing the LaF3 / PAN@Zn metal negative electrode according to claim 1, characterized in that: The preparation method of the nano-LaF3 comprises the following steps: mixing lanthanum nitrate hexahydrate, deionized water, a surfactant and ammonium fluoride, performing a hydrothermal reaction, and then performing centrifugal washing and drying to obtain the nano-LaF3, wherein the particle size of the nano-LaF3 is 10-20 nm.
6. The method for preparing the LaF3 / PAN@Zn metal negative electrode according to claim 5, characterized in that: The surfactant is polyethylene glycol or hexadecyltrimethylammonium bromide.
7. The method for preparing the LaF3 / PAN@Zn metal negative electrode according to claim 6, characterized in that: The molar ratio of the lanthanum nitrate hexahydrate, ammonium fluoride and surfactant is 1:(3-6):0.1; the temperature of the hydrothermal reaction is 70-80°C and the time is 12-15 hours.
8. The LaF3 / PAN@Zn metal anode prepared by the method according to any one of claims 1 to 7, characterized in that: The LaF3 / PAN@Zn metal negative electrode is a LaF3 / PAN electrospun nanofiber membrane in situ modified on the surface of the metal zinc negative electrode.
9. The LaF3 / PAN@Zn metal negative electrode according to claim 8, characterized in that: The thickness of the LaF3 / PAN electrospun nanofiber membrane is 70-80 μm.
10. Use of the LaF3 / PAN@Zn metal negative electrode according to claim 8 or 9 in an aqueous zinc ion battery.
Citation Information
Patent Citations
Polymer coating modified zinc negative electrode and preparation method and application thereof
CN114792775A
Modified zinc negative electrode plate capable of inhibiting dendritic crystal growth, preparation method and application of modified zinc negative electrode plate
CN117542947A
Cited By
Zinc negative electrode modified by telescopic gel interface layer as well as preparation method and application of zinc negative electrode
CN121709515A
